Phosphorus Extraction from Soil Constituents Using Bray P-1, Mehlich-1 and Olsen Solutions - Jamalam Lumbanraja; Sri Mulyani; Muhajir Utomo; Sarno Sarno (JOURNAL OF TROPICAL SOILS, 2017)
The extraction methods using Bray P-1, Mehlich-1, and Olsen solutions are the most frequently used in equilibrium condition to estimate the available P in the soil constituents. However, each method can gives some different values that may not describe the availability of soil P. Therefore, it is necessary to conduct a laboratory experiment to compare the three solutions in equilibrium and kinetics conditions for P release from soil colloids as a basic data for the future related to plant productions. The objective of this study was to compare the amounts of P release in equilibrium and kinetics conditions using Bray P-1, Mehlich-1, and Olsen solutions and the rate constants (k) of P release from soil colloids using the three solutions of five soil constituents or treatments: (1) Soil (100% soil), (2) P-rock (100% phosphate rock), (3) compost (100% chicken manure compost), (4) soil + P-rock (75% soil + 25% phosphate rock), and (5) soil + P-rock + compost (50% soil + 25% phosphate rock + 25% chicken manure compost). Each extraction for each treatment was conducted in triplicate. The results indicate that the amounts of extracted P employing equilibrium condition in all treatments are significantly lower compared to those employing kinetics condition. The results also show that Mehlich-1 solution is the most powerful solution to extract P from soil constituents followed by Bray P-1 solution and Olsen solution, except that in the soil + phosphate rock + compost treatment in which the amount of P extracted using Mehlich-1 solution is the highest then followed by that of P extracted by Olsen solution and Bray P-1 solution both in equilibrium and kinetic conditions. The highest rate constants (k) of the reaction in all treatments were found in the extractions using Mehlich-1 solution for desorbed P followed by that of using Bray P-1 solution and Olsen solution. Keywords: Compost, equilibrium, kinetics, P extraction solutions, phosphate rock, soil